2013
DOI: 10.1371/journal.pone.0081795
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intra-Abdominal Hypertension on the Secretory Function of Canine Adrenal Glands

Abstract: Intra-abdominal hypertension (IAH) can damage multiple organ systems, but the explicit impact on the adrenal gland is unclear. To evaluate the effects of intra-abdominal pressure (IAP) on the secretory function of the adrenal glands, we established canine models of IAH. By comparing morphology; hemodynamics; plasma cortisol, aldosterone, epinephrine, and norepinephrine concentrations; and the expression of IL-1, IL-6, and TNF-α in adrenal gland tissue from these dogs, we found that hemodynamic instability occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Besides the cardiac sympathetic nerve activity, other factors may be involved in such as catecholamine-induced arrhythmia. There was a study which reported that enhanced intra-abdominal pressure either from mass or other abdominal pathologies positively correlated with hormone secretion including catecholamine from the adrenal gland [ 44 ].…”
mentioning
confidence: 99%
“…Besides the cardiac sympathetic nerve activity, other factors may be involved in such as catecholamine-induced arrhythmia. There was a study which reported that enhanced intra-abdominal pressure either from mass or other abdominal pathologies positively correlated with hormone secretion including catecholamine from the adrenal gland [ 44 ].…”
mentioning
confidence: 99%
“…This hormone can affect the functioning of the heart and blood vessels, and increases blood pressure on a regular basis (20). Our results suggest significant differences in the stress level as mild, moderate and severe between the normotensive and hypertensive groups.…”
Section: Discussionmentioning
confidence: 55%